The Effect of Bismuth as A Local Hemostatic Material Post Extraction of Permanent Mandibular First Molars Teeth - Monika Elidasari; Moh Basroni Rizal; Yulie Emilda Akwan (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2024)
Background: Bleeding is a post-extraction complication that is often found in dentistry. Normally post-extraction bleeding stops 12-24 hours after surgery, but it is often found for more than 24 hours. The post-extraction bleeding usually stops by pressing the area with sterile gauze but there is an obstacle due of the large volume of blood. Objective: to evaluate the bismuth subgallate as an effective local hemostatic agent. Methods: This study conducted on patients who came to the Oral Surgery Clinic, Nala Husada Hospital Surabaya, population aged 18-60 years, with permanent mandibular first molars diagnosed with chronic apical periodontitis et causa pulp gangrene or radix gangrene without systemic disorder and planned for extraction teeth with close method. It was divided into 2 groups by simple random sampling group design; the control group and the treatment group. After tooth extraction with the close method, a local hemostatic agent will be applied at the socket. The control group used a paste containing vaseline, while the treatment group used a paste containing bismuth subgallate. This paste contains 2.25% bismuth subgallate mixed with Peruvian balsam. After the application of local hemostatic agents, both the control group and the treatment group will be calculated the bleeding time, bleeding volume, and whether or not the secondary bleeding occurs. Conclusion: of this study is that bismuth subgallate has an effect as a local hemostatic agent after extraction of the mandibular first permanent molars.